The Propagators for δ and δ′ Potentials With Time-Dependent Strengths - Erman, Fatih; Gadella, Manuel; Uncu, Haydar (Frontiers in Physics, 2020)
We study the time-dependent Schrodinger equation with nite number of Dirac δ andδ' potentials with time dependent strengths in one dimension. We obtain the formal solution for generic timedependent strengths and then we study the particular cases for single delta potential and limiting cases for finitely many delta potentials. Finally, we investigate the solution of time dependent Schrödinger equation for δ' potential with particular forms of the strengths.